Oil conflict and compromises in the Ecuadorian Amazon: the relationships between oil and indigenous people in historical perspective (Alternautas, 2023)
This paper retraces the history of the relationships between indigenous people and the oil industry in Ecuador in three chronological stages: 1) unregulated and uncompensated oil development (and conflict) between the 1970s and the 1990s, 2) social compensation, material needs, and compromises at the local level starting in the 1990s, and 3) the decade of Correa’s presidency (2007–2017), marked by a new extractive compromise which emphasizes the need for oil extraction to provide people with health and education, and the institutionalization of an unfair local dilemma between environmental protection and socio-economic benefits, recorded through sometimes dubious processes of prior consultation. This account sheds light on some of the mechanisms through which open conflicts can turn (and have turned, in the Ecuadorian case) into compromises and acceptance; as the supply of powerful actors, such as large oil companies and States, meet the demands of marginal populations for necessary basic services and other socio-economic benefits which are otherwise lacking. It is a reminder that acceptance (by the local people) does not mean the situation is acceptable. Instead, it may hide cases of environmental injustice – which we more often associate with open conflict – and result in indigenous communities being left out of the analysis. This account points to the urgency of finding post-extractive development alternatives, both at the local and national levels.